2020
DOI: 10.3390/ijerph17134711
|View full text |Cite
|
Sign up to set email alerts
|

A Resourceful Work Environment Moderates the Relationship between Presenteeism and Health. A Study Using Repeated Measures in the Swedish Working Population

Abstract: The objective of this study was to investigate if the psychosocial work environment moderates the proposed negative impact of presenteeism on future general health. We expect that the negative impact of presenteeism on general health is weaker if the psychosocial work environment is resourceful, and more pronounced if the environment is stressful. Data were derived from the 2008–2018 biennial waves of the Swedish Longitudinal Occupational Survey of Health (SLOSH). The final analytic sample consisted of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…As highlighted by Karanika-Murray and Biron (2020) , presenteeism is a dynamic process that involves an interaction between individuals, their working environment, and the broader context, and that its consequences (positive and negative) can co-occur. Our results also reflect the study by Bergström et al (2020) who showed that despite having negative effects on health in the long-term, working while ill in a resourceful environment can buffer its consequences.…”
Section: Discussionsupporting
confidence: 90%
“…As highlighted by Karanika-Murray and Biron (2020) , presenteeism is a dynamic process that involves an interaction between individuals, their working environment, and the broader context, and that its consequences (positive and negative) can co-occur. Our results also reflect the study by Bergström et al (2020) who showed that despite having negative effects on health in the long-term, working while ill in a resourceful environment can buffer its consequences.…”
Section: Discussionsupporting
confidence: 90%
“…As such, it is possible to facilitate movement from dysfunctional to functional presenteeism by building the right workplace climate conditions. The findings concur with research on the importance of climate for work behaviour, often over and above the job level (Karanika- Murray, Michaelides, & Wood, 2017), and on the crucial role of a resourceful work environment (Bergström, Gustafsson, Aboagye, Marklund, Aronsson, Björklund, & Leineweber, 2020). In conclusion, presenteeism behaviour is a function of the person (i.e., their inclinations, health condition, work demands, past behaviour) and their environment (i.e., the PSC climate and job characteristics).…”
Section: The Role Of the Work Environment For Presenteeismsupporting
confidence: 86%
“…The present findings showed that nurses' job demand was the main cause that affected their presenteeism. Therefore, it may be a reliable approach to reduce presenteeism and its cost by increasing individual job resources and psychological resources ( 37 ). Furthermore, more intervention programmes on presenteeism are suggested based on the theory.…”
Section: Discussionmentioning
confidence: 99%